Strategi Komunikasi Keluarga pada Anak Toxic Relations Broken Home dalam Membentuk Karakter Sosial - Alpi Syahrin Sagala; Zuhriah (Institut Agama Islam Negeri Ponorogo, 2024)
Families, especially parents, have an important influence in shaping children's character, especially when character development starts at an early age. Family communication refers to the exchange of information and ideas among family members. This communication serves as a means for family members to engage with each other and plays an important role in the formation and development of values that guide life. This qualitative research uses in-depth interviews with self-disclosure theory to examine family communication strategies in dealing with toxic relationships in broken home families and the impact of broken homes on toxic relationship parenting on child development. Conflict causes family disharmony, while toxic relationships and poor parenting imply poor parenting. The study found that children from broken home families have lower self-esteem, decision-making problems, guilt, and mental health problems. In this case the findings regarding family communication strategies highlighted interpersonal communication and understanding of healthy parenting practices and the role of parents in children's development. Broken home families communicate using cell phones and social media, rarely speaking to each other. Even for certain issues, parents have to meet. There are no communication difficulties with the community, there are only psychological barriers due to shyness in broken home families when socializing. Parent education, psychotherapy and parenting education are suggestions. These measures can prevent toxic relationships and help psychologically damaged children